PKM Peningkatan Keahlian Ibu PKK di Desa Karanganyar dengan Memanfaatkan Sumber Daya Alam (SDA) melalui Olahan Abon Ikan Laut dan Nugget - M Syafiih; M. Fadhilur Rahman; Firjon Siyasi (Universitas Nurul Jadid, 2020)
Karanganyar is a village with huge result of seafoods, since the most of inhabitants are traditional fishermen. Their livelihoods are mackerel tuna (ikan tongkol) with 100 tons for each fish season. However, the price of fresh tuna is too cheap, because they sell uncooked tuna in common markets. The lack of knowledge on processing the uncooked tuna with simple technology is contributing on the ways they have no idea to increase their income from the the kinds of seafood. This article figures out an alternative way of diversification of tuna into floss and nugget which aims to increase their income, to provide a skill of enterpreneurship, and to reduce number of unemployment in Karanganyar. The subject of this program is a Women Team of Empowerment and Family Welfare (Ibu Pemberdayaan Kesejahteraan Keluarga) because they are potentially able to practice this diversification and responsible to help their husbands in increasing the family welfare.